Painting background - Son Nguyen (22474540) (2025)
While working on the PI's commissioned sign, assisted by his employee Artist Thông, Artist Thuyên explains the various layers of colour that he applies and the techniques he uses to make the background look 'distressed' and achieve an overall retro feel. He also raises background colour choice in the context of phong thủy (feng shui).